EIGHTH-GRADE STUDENTS’ ERRORS AND MISCONCEPTIONS REGARDING OPERATIONS WITH ALGEBRAIC EXPRESSIONS - Aydın Güç, Funda; Aygün, Derya (International Online Journal of Education and Teaching, 2021)
The study aims to determine the mistakes made by students in operations with algebraic expressions and the misconceptions that lead to errors. To determine students’ errors and misconceptions, the “Misconceptions Diagnostic Test for Operations with Algebraic Expressions” was developed by the researchers, considering the curriculum, relevant literature, and researchers’ teaching experience. The diagnostic test included 10 open-ended questions. The test was applied to 48 eighth-grade students. Clinical interviews were conducted with all students on their wrong answers. Results indicated that the most common misconception is that the minus at the beginning of the algebraic expression has no meaning and that half of the students have this misconception. It has been observed that the number of students with the following misconceptions are close to each other: “The operation on one side of the equation should also be applied to the other side so that the equality is not broken”, “we should take into account the order of operation priority in integers while writing the sentences as algebraic expressions,” and “everything before the parenthesis is distributed to the parentheses.” Furthermore, the reasons for the emergence of these misconceptions are epistemological barriers and over-generalization of information in arithmetic.